2012
DOI: 10.31018/jans.v4i2.240
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase and microbial inhibitory activities of Tetrapleura tetraptera

Abstract: Abstract:The cholinesterase and microbial inhibitory activities of different parts of Tetrapleura tetraptera plant were evaluated due to their local applications. The cholinesterase results revealed that the extracts showed some levels of inhibitory effects depending on the solvents used. Tetrapleura tetraptera leaves had better inhibitory effects with maximum inhibitory activity of 70.0% at a concentration of 1.00mg/l for the water extract. Tetrapleura tetraptera bark showed highest inhibitory effect of 71.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…The phytochemical analysis of the chloroform fraction revealed the presence of alkaloid, tannin, flavonoid, phenol, saponin and coumarin. The presence of these families of compounds in fraction confirms the results of previous studies on the extracts of I. gabonensis [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. These phytochemicals confirm the pharmacological properties reported previously such as anti-ulcer and anti-diarrhoea [23], antioxidant [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], anti-inflammatory [6], anti-cancer [25] and anti-microbial activities [11][12][13][14][15]…”
Section: Phytochemical Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…The phytochemical analysis of the chloroform fraction revealed the presence of alkaloid, tannin, flavonoid, phenol, saponin and coumarin. The presence of these families of compounds in fraction confirms the results of previous studies on the extracts of I. gabonensis [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. These phytochemicals confirm the pharmacological properties reported previously such as anti-ulcer and anti-diarrhoea [23], antioxidant [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], anti-inflammatory [6], anti-cancer [25] and anti-microbial activities [11][12][13][14][15]…”
Section: Phytochemical Analysissupporting
confidence: 89%
“…The result obtained reveals highest antifungal activity value against C. albicans at 2.5 mg/mL (5 mm) and lowest activity value for C. albicans at 25 mg/mL (14 mm). The MIC values obtained in this study are compared favourably with those reported in the literature for some of the test organisms [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Figs (3 and 4) show the MIC charts for both bacteria and fungi against the chloroform fraction.…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 71%
See 1 more Smart Citation
“…The stem-bark of T. tetraptera has been shown to possess antiulcerative, antibacterial and antioxidant potential that could be attributed to a wound healing potential [ 13 , 19 , 20 ]. On this basis, the present study was designed to evaluate the wound healing effect of the water extract of the bark on excisional and incisional wound models.…”
Section: Discussionmentioning
confidence: 99%
“…These spices have shown promise in the inhibition of microbial growth. Okoronkwo and Echeme (2012) reported that extracts of T. tetraptera effectively inhibited the growth of E. coli, S. aureus and Proteus mirabilis with resultant zones of inhibition of 5.00 -18.00 mm for the leaves, stem, bark and roots etc [25]. indicating that extracts of T. tetraptera can be bacteriostatic/bacteriocidal against these test pathogens.…”
Section: Citationmentioning
confidence: 99%